Chromosome studies of males in an institution for the mentally handicapped. - English, C J (1989)
Karyotypes were examined in 512 (91.9%) of 557 male patients in an institution for the mentally handicapped. A total of 110 (21.5%) had an abnormal karyotype: 65 (12.7%) with Down's syndrome, 30 (5.9%) with the fragile X syndrome, 13 (2.5%) with autosomal anomalies other than Down's syndrome (12 unbalanced, one balanced), and two (0.4%) with sex chromosome anomalies.